Motion effects in proton treatments of hepatocellular carcinoma—4D robustly optimised pencil beam scanning plans versus double scattering plans. (23rd November 2018) - Pfeiler, Tina; Ahmad Khalil, Dalia; Ayadi, Myriam; Bäumer, Christian; Blanck, Oliver; Chan, Mark; Engwall, Erik; Geismar, Dirk; Peters, Sarah; Plaude, Sandija; Spaan, Bernhard; Timmermann, Beate; et al.
Abstract: Pencil beam scanning (PBS) proton therapy enables better dose conformality for complex anatomical geometries than passive proton scattering techniques, but is more susceptible to organ motion. This becomes an issue when treating moving tumours in the thorax or abdomen. Novel four-dimensional treatment planning approaches have been developed to increase the robustness of PBS plans against motion. However, their efficacy still needs to be examined by means of 4D dynamically accumulated dose (4DDD) analyses. This study investigates the potential use of 4D robust optimisation to maintain sufficient target coverage in the presence of organ motion, while sparing surrounding healthy tissue, for hepatocellular carcinoma (HCC). The liver is particularly suited to study motion interplay effects since the treatment region exhibits smaller density gradients and more homogeneous tissue than targets in the thorax, making it less prone to range errors. A facility-specific beam time model, developed and experimentally validated previously, was used for the clinical evaluation. 4DDD analyses of eleven target volumes did not show a significant improvement of the target coverage using 4D robust optimisation, but a reduction of the dose to close-by organs at risk. Interplay effects were averaged out for the applied fractionation scheme of 15 fractions. Contrary to PBS, passive double scattering (DS) plans yielded homogeneous 4DDD dose distributions in a single fraction. But, in some cases, they exceeded organ at risk dose limits, which were only satisfied in PBS. The average normal liver dose could be decreased by almost 6% compared to non-robustly optimised PBS plans and by 16% compared to DS plans when implementing 4D robust optimisation. Except for some very small tumours with large motion amplitudes, 4D robustly optimised PBS plans were found to be clinically acceptable even without supplementary motion mitigation techniques.